Public Participation and Policy Implementation: Evaluating the Effectiveness of Community Involvement in Local Development Programs - Muhtar; Kumalasari, Intan; Dewi, Erlita Khrisinta (Malaqbi Publisher, 2025)
This study investigates the influence of public participation on the effectiveness of policy implementation in local development programs. Grounded in participatory governance and policy implementation theories, the research explores how community involvement, institutional capacity, and inclusiveness contribute to successful local development outcomes. Using a quantitative research design, data were collected from local government officials, community representatives, and program participants to assess the relationships among public participation, accountability, transparency, and policy performance. The results reveal that meaningful community participation significantly enhances implementation effectiveness by improving coordination, strengthening trust, and aligning development initiatives with local needs. Furthermore, institutional capacity and communication quality were found to moderate the impact of participation on implementation outcomes, emphasizing that participatory mechanisms are most effective when supported by capable institutions and transparent governance systems. However, the study also identifies persistent barriers such as elite capture and limited local empowerment, which can reduce participation’s transformative potential. These findings highlight the importance of embedding participatory practices within local governance frameworks to achieve more sustainable, inclusive, and community-centered development. The study contributes to both academic discourse and practical policymaking by offering evidence-based recommendations for enhancing the design and implementation of participatory local development programs.